A 5-year strategic plan for Tecson Enterprises directions for the future - Guerrero, Gretel A. (School of Management, University of the Philippines Mindanao, 2012)
Up to the year and beyond, population of the region is expected to grow every year with an inverse relationship with food production. Closing this gap and increasing food production will require intensive agriculture based on modern technologies, including fertilizers and pesticides. Such changes are particularly important because the region is still in the position to increase and heighten its land use and productivity. With the vastness of land areas, farmers are confronted to remedy low soil fertility through fertilizer application to increase soil management practices. Farmers are also forced to protect their crops against plant diseases and insect infestation from planting to harvest. The increased use of fertilizer and pesticide has a big impact to the enterprise profitability and sustainability. A strategic direction is needed in order to secure the enterprise?s stability in an industry which is conducive to change. Such plan is essential to maintain the growth of the enterprise to help small-scale farmers increase their production and sustain its responsibility to protect the environment. With the help of the different methods, techniques and framework of Fred R. David, an important strategic option was formulated and determined. It is recommended that the enterprise will concentrate its resources in the existing markets and will gradually expand to new territories. This leads to the prevailing theory that companies will eventually differentiate when they have excess resources, capabilities, and core competencies.